Comportamento térmico de coberturas em camadas duplas e estudo da substituição da cama por piso plástico na qualidade do ar, desempenho e índice de lesões em frangos de corte - Almeida, Eduardo Alves de [UNESP] (2014)
The cover has a fundamental role in a facility, being able to prevent much of the solar radiation to penetrate and raise your temperature. This experiment was conducted at UNESP in Jaboticabal, with the objective of evaluating the efficiency of the installation of two types of toppings (Metallic and Fibercement) in single and double layers, varying spacing between double layers of 1cm to 5cm. As repetition was adopted the collection days and the number of prototypes, totaling 30 replicates for each treatment (2 prototypes x 15 collection days). In total 12 treatments were used (tile x spacing ) with two prototypes for each treatment. Temperature sensors were installed on the bottom of the cover and the center of the model, obtaining the internal surface temperature of the covers (IST) and the ambient temperature (AT) inside the model. The data were analyzed using the PROC MIX SAS (Statistical Analysis System), considering the schedules for each day of measurement assessed with variance analysis performed and Scott-Knott test at 1% significance. For IST we observed a difference of 11.3 °C at 14h between simple metal tile (42.9 °C) and double layer with 5cm spacing (31.6 °C), and difference of 7.6 °C between simple tile fiber cement (39.3 °C) and 5cm between double layers (31.7 °C). For AT was observed maximum value for the simple metal tile (36.1 °C) and minimum for the spacing of 5cm between double layers (30.8 °C). For fiber cement, was observed for single layer 35.4 °C and spacing of 5 cm 30.9 °C. The use of metal tile and fiber cement double layers was efficient in promoting a decrease in the values of IST and AT in this model